Evolution and participation - Poli, Roberto (Pensamiento. Revista de Investigación e Información Filosófica, 2010)
Professor Roberto Poli’s view is founded on his research background: ontology and system theory. His systemic ontology offers a unitary and holistic approach to understand reality and, most specifically, life. This professor highlights the concepts of anticipation (ability to behave taking into account possible future states), autopoiesis (systems capable of reproducing the components of which they are composed) and self-referentiality (the system’s relational self-production governs its capacity to have contacts with the environment) as important characteristics of the life systems. Thus, the seminar began with a discussion of the essential characteristics of life – in relation to the classical question what is life? — from an ontological perspective using the conceptual framework of the theory of systems and the relational biology (among others). This discussion has become the first step in our search for the origin and nature of reason, as a special feature that emerged evolutionary within the realm of life.